Feasibility study of triboelectric nanogenerator utilizing the empty fruit bunch (EFB) fiber of palm tree - Al-Nuaimi, Yasir Ja'fer Awad; Supeni, Eris E.; Salleh, Hanim; Al-Ashtari, Waleed K.; A. Azizi, Muhammad; Abdul Rahim, Sharafiz (Praise Worthy Prize S.r.l, 2024)
– This paper studies the feasibility of using agricultural waste in designing the triboelectric nanogenerator based on energy harvesting. The motivation behind this work is to utilize the EFB fiber waste of Oil Palm and Date Palm as a bio-based triboelectric surface in order to generate electricity for low-power self-powered sensor applications. Therefore, the main purpose of this paper is to present a new material extracted from agricultural waste and tree droppings for using in the field of mechanical energy harvesting, and whether the above-mentioned fiber waste can be used as a bio-based triboelectric layer within energy harvesting techniques for industrial applications or not. In addition, the study has determined which is the most efficient material from between PVC and PTFE, to be used in the manufacture of the harvester structure. For testing the effectiveness of the EFB fibers working as B-TENG, they were tested in their natural state without any additions or operation of washing, sifting, or mixing with other materials. The biomaterial layers used were attached to a designed harvester as a triple cantilever beam in a trapezoidal shape. The main used biomaterials for the harvester were the Date Palm EFB fibers and Oil Palm EFB fibers in order to evaluate their performance and efficiency. The effect of the bio-layer dimensions on the amount of energy produced was studied, as well as the efficiency of each of the EFB fiber types for the oil palm and the date palm, in addition to the efficiency of each of PVC and PTFE material when using each of them in manufacturing the structure of the harvester. The results showed that increasing the dimensions of the used B-TENG leads to improve the output voltage. The output voltage increased when Date Palm fibers were used from 7.03 V to 10.59 V at the frequency of 30 Hz when its surface area was increased from 2 cm × 3 cm to Full trapezoidal area. The study also showed the superiority of the PVC material over the PTFE material when using each separately in the manufacture of the harvester frame. When using Oil Palm fibers as a biomaterial layer, when placed on the harvester made of PVC, the resulting voltage was about 6.15 V at the frequency of 35 Hz while the resulting voltage when used with the harvester made of PTFE is 0.21 V at the frequency of 30 Hz. The study also showed that the Date Palm fibers produced a better output voltage than the Oil Palm fibers. When both materials were used with a harvester made of PVC material separately, the Date Palm fibers produced an output voltage of 10.59 V at the frequency of 30 Hz while the Oil Palm fibers produced a voltage of 6.15 V at the frequency of 35 Hz. Copyright © 2024 Praise Worthy Prize S.r.l.-All rights reserved.